2020
DOI: 10.1002/cctc.202000426
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Porous Configurated Ni2P/Ni Foam Catalyst and its Boosted Properties for pH‐universal Hydrogen Evolution Reaction and Efficient Nitrate Reduction

Abstract: Nickel phosphide (Ni 2 P) has been widely explored toward hydrogen evolution reaction (HER) for desirable durability and high performance. Tuning the electronic structures and morphologies of Ni 2 P plays a pivotal role in the improvement of HER performance. In this work, three Ni 2 P catalysts were fabricated by different strategies and their HER properties were compared. It was found that the bicontinuous porous structured Ni 2 P on Ni foam (Ni 2 P /NFÀ EHP) prepared using coupled electroless nickel-phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 81 publications
2
21
0
Order By: Relevance
“…A pseudofirst-order kinetic rate law was derived and linearly fitted to obtain the apparent rate constant (K ap ) (Figure 3e). 30,31 The K ap value of Cu-N 4 /P was 8.8 times larger than that of Cu-N 4 , indicating that the reaction rate was significantly enhanced. Stability is one of the important parameters of an electrocatalyst and determines to some extent whether it has a real economic value or not.…”
Section: Methodsmentioning
confidence: 97%
“…A pseudofirst-order kinetic rate law was derived and linearly fitted to obtain the apparent rate constant (K ap ) (Figure 3e). 30,31 The K ap value of Cu-N 4 /P was 8.8 times larger than that of Cu-N 4 , indicating that the reaction rate was significantly enhanced. Stability is one of the important parameters of an electrocatalyst and determines to some extent whether it has a real economic value or not.…”
Section: Methodsmentioning
confidence: 97%
“…So far, advanced works indicate that non-noble metal nanostructures (such as copper, titanium, iron, nickel, cobalt, etc.) also reveal high electroactivity for the NIT-ERR.…”
Section: Introductionmentioning
confidence: 99%
“…Since transition metal phosphides have excellent electroactivity for a hydrogen evolution reaction (HER), they may effectively electrocatalyze the NO 3 – -ERR. In fact, recent reports have demonstrated that Ni 2 P nanomaterials have obvious electroactivity for NO 3 – -ERR. , Although cobalt phosphide (CoP) nanomaterials also have Pt-like electroactivity for HER, ,, no work about NO 3 – -ERR at CoP nanoparticles is reported till now.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recent reports have demonstrated that Ni 2 P nanomaterials have obvious electroactivity for NO 3 − -ERR. 29,30 Although cobalt phosphide (CoP) nanomaterials also have Pt-like electroactivity for HER, 20,31,32 no work about NO 3…”
Section: Introductionmentioning
confidence: 99%